Gene Cloning, Expression, and Characterization of a beta-Agarase, AgaB34, from Agarivorans albus YKW-34 - Fu, Xiao Ting; Pan, Cheol-Ho; Lin, Hong; Kim, Sang Moo (KOREAN SOC MICROBIOLOGY & BIOTECHNOLOGY, 2009)
A beta-agarase gene, agaB34, was functionally cloned from the genomic DNA of a marine bacterium, Agarivorans albus YKW-34. The open reading frame of agaB34 consisted of 1,362 by encoding 453 amino acids. The deduced amino acid sequence, consisting of a typical N-terminal signal peptide followed by a catalytic domain of glycoside hydrolase family 16 (GH-16) and a carbohydrate-binding module (CBM), showed 37-86% identity to those of agarases belonging to family GH-16. The recombinant enzyme (rAgaB34) with a molecular mass of 49 kDa was produced extracellularly using Escherichia coli DH5 alpha as a host. The purified rAgaB34 was a P-agarase yielding neoagarotetraose (NA4) as the main product. It acted on neoagarohexaose to produce NA4 and neoagarobiose, but it could not further degrade NA4. The maximal activity of rAgaB34 was observed at 30 degrees C and pH 7.0. It was stable over pH 5.0-9.0 and at temperatures up to 50 degrees C. Its specific activity and k(cat)/K-m value for agarose were 242 Wing and 1.7x10(6)/sM, respectively. The activity of rAgaB34 was not affected by metal ions commonly existing in seawater. It was resistant to chelating reagents (EDTA, EGTA), reducing reagents (DTT, beta-mercaptoethanol), and denaturing reagents (SDS and urea). The E. coli cell harboring the pUC18-derived agarase expression vector was able to efficiently excrete agarase into the culture medium. Hence, this expression system might be used to express secretory proteins.
Keywords: DEEP-SEA MICROBULBIFER; SP STRAIN PO-303; ESCHERICHIA-COLI; MARINE BACTERIUM; ENZYMATIC-PROPERTIES; PURIFICATION; PROTEIN; HYDROLYSIS; SECRETION; SEQUENCES